Audacious euphony chromatic harmony and the triad's second nature - Cohn, Richard Lawrence 1955- (Oxford studies in music theory, 2012)
Reconstructing historical conceptions of harmonic distance 'Audacious Euphony' advances a geometric model appropriate to understanding triadic progressions characteristic of 19th-century music